AN APPROACH TO INTERSEXUALITY IN COSTARICA FROM BIOETHICS AND HUMAN RIGHTS - Alvarado Acuña, José Joaquín (2018)
The main problem addressed in this article starts in the concern about the lack of information and care protocols for intersex people, especially minors or newborns, their social invisibility, the stigma hanging over them and the medicalization and pathologization of intersex individuals, thereby producing its objectifcation and dehumanization.